Konsep Evaluasi Pembelajaran Menurut Surah Ali Imran Ayat 200 (Studi Pemikiran Al-Ghazali dalam Ihya Ulumuddin) - Abdurrahman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Verse 200 of Ali Imran's letter, although it does not explicitly mention assessment as Learning (AaL), is interpreted by Al-Ghazali in Ihya Ulumuddin (IU) as a murabathah system that includes six phases. This paper aims to confirm this interpretation with various general theories about the latest AaL challenges, and to build a construction of the interpretation of Al-Ghazali's AaL concept. The method used is library research with a content analysis approach, de-contextualization, and re-contextualization analysis techniques, as well as basic inductive techniques. Research findings state that Al-Ghazali's interpretation of AaL is in line with the latest AaL theory, such as AaL based on SRL (self-regulation of learning), especially based on co-regulation of learning with four main phases: forethought, planning and activation, monitoring, control, reaction, and reflection. Apart from that, it is also in line with formative and summative evaluation theories, as well as theories about feedback. In the area section, AaL Al-Ghazali's interpretation is in line with the areas of cognition, motivation/affect, behavior, and context. This research also succeeded in developing the construction of Al-Ghazali's AaL system which consists of: musyarathah, muraqabah, muhasabah, mu’aqabah, mujahadah and mu’atabah into concrete form.